PENGARUH ALGORITMA INISIALISASI NGUYEN-WIDROW TERHADAP ALGORITMA BACKPROPAGATION DALAM PREDIKSI INDEKS HARGA KONSUMEN (IHK) - HAFIZH FARUQ MAHFUZH (2020)
One of the price indexes that is often used to measure inflation is the Consumer Price Index (CPI). The prediction results of the Consumer Price Index (CPI) can help various parties in planning economic strategies in their business, and also be a reference for making price policies. The method that can predict the value of Consumer Price Index (CPI) is Artificial Neural Network (ANN) with Backpropagation algorithm. The method has two ways in determining the initial weight, namely using random numbers and using the Nguyen-Widrow algorithm. The purpose of this study was to determine performance of the Backpropagation algorithm in predicting the Consumer Price Index (CPI) with initial weights using Random numbers and Nguyen-Widrow algorithm. The results of the Backpropagation algorithm performance testing when achieving convergence, obtained the number of iterations 9086 from the initial weight of random numbers, while for the initial weight of Nguyen-Widrow 3625 iterations were obtained. The MSE and the coefficient of determination test results of 24 experiments, it is known that the Nguyen-Widrow Initialization has an MSE value 0,0001145 and the coefficient of determination 0,99778. Whereas the random initialization has an MSE value 0,000143 and a coefficient of determination value 0.99445